A Discriminant Analysis Approach to Predict the Performance of Joint Venture General Insurance Companies in Indonesia - Moses P S (NIM 19014070), Gerard
ABSTRACT Insurance industry plays a very important role to the national economy of Indonesia. Nonetheless, the competition in general insurance sector disposed to become fiercer for the past few years, especially in the joint venture companies side. To survive and win in a very competitive industry, a company must perform well and much better than the competitors. The objective of this paper is to formulate a measurement tool which can measure and predict the performance of a joint venture general insurance company in Indonesia as well as to distinguish between a group of companies which perform well and which do not perform well. The samples used in this analysis are taken from all of the 16 joint venture general insurance companies in Indonesia (total sampling) and the data used is based on the period of 2011-2015. The method used in this analysis is the Discriminant Analysis method which uses statistical techniques and combined financial ratios model that can be used as one of the appropriate approach to predict the performance of insurance company. The result of the analysis suggests that the management of the joint venture general insurance company in Indonesia must thoroughly understand the six selected financial ratios, those are Debt Ratio, Return on Assets, Net Profit Margin, Level of Claim Settlement, Combined Ratio and Average Collection Period. The analysis result can be used as a guidance to improve the companyÃ‚Â’s performance in order to be able to survive and win in the highly competitive industry in joint venture general insurance sector in Indonesia. key words: financial performance, financial ratio, joint venture general insurance company, discriminant analysis